Junior female athletes` competitive fitness analysis - Platonov, D. N.; Platonova, Z. N. (Theory and Practice of Physical Culture, 2020)
Competitive fitness may be defined as the sport-specific optimal individual status measurable by the relevant physical, emotional and thinking capacity rates.